2012 35th International Conference on Telecommunications and Signal Processing (TSP) 2012
DOI: 10.1109/tsp.2012.6256346
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different walking speeds and surfaces on accelerometer-based biometric gait recognition

Abstract: This paper gives an insight about the influence of different walking speeds (slow, normal and fast) and surfaces (flat carpeted, grass, gravel and inclined) on gait recognition. Gait recognition is a type of biometric authentication that operates on behavioral characteristics of human beings. This research utilizes wearable sensors, and we have used a commercially available mobile device. Gait data is collected from 48 subjects for six different walk settings in two sessions on different days to measure same-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…For determining gait characteristics, they asked each participant to walk across the surface with their normal pace. Other studies such as presented in [12,31,32] have also demonstrated the influence of surface.…”
Section: Related Workmentioning
confidence: 83%
“…For determining gait characteristics, they asked each participant to walk across the surface with their normal pace. Other studies such as presented in [12,31,32] have also demonstrated the influence of surface.…”
Section: Related Workmentioning
confidence: 83%
“…For our experiments, we used the same data set as employed in [21]. This biometric gait data was collected using an Android phone Google G1.…”
Section: Description Of Dataset Usedmentioning
confidence: 99%
“…We used only x-axis data for our experiments because it is more discriminant as compared to y and z-axis [21]. One recorded file contains two walks as shown in figure 3.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…To overcome this situation, the obtained data need to be increased its sampling rate depending on the number of samples per second (Hz) which also called as interpolation. According to [11], there are generally 2 methods in implementing interpolation on the gait signal which is linear [12][13][14][15][16][17][18] and cubic spline [12]. There are also papers that do not mentioned the use of any interpolation in gait application [19][20].…”
Section: Introductionmentioning
confidence: 99%